Complications in the treatment of periprosthetic joint infection of the hip: when do they occur? - K. Li; M. Cuadra; G. Scarola; S. Odum; S. Odum; J. Otero; J. Otero; W. Griffin; B. D. Springer; B. D. Springer (Journal of Bone and Joint Infection, 2021)
Prosthetic joint infection (PJI) is a devastating complication after total hip arthroplasty (THA). The common treatment in the USA is a two-stage exchange which can be associated with significant morbidity and mortality. The purpose of this study was to analyze complications in the treatment course of patients undergoing two-stage exchange for PJI THA and determine when they occur. Methods: We analyzed all patients that underwent two-stage exchange arthroplasty for treatment of PJI after THA from January 2005 to January 2018 at a single institution. Complications were categorized as medical or surgical and divided into interstage and post-reimplantation. Minimum follow-up was 1 year. Success was based on the MusculoSkeletal Infection Society (MSIS) definition. Results: 205 hips (203 patients) underwent first stage of planned two-stage exchange. The median age was 68 (interquartile range (IQR) 18). There were 97 males and 106 females. Overall, 73/205 (38 %) patients had at least one complication during treatment: 13.5 % (25/185) of patients experienced a medical complication and 28.1 % (52/185) a surgical complication; 2.4 % died within 1 year of surgery, and 4.9 % (15/203) had mortality at a median of 2.5 years (IQR 4.9); 27 % of patients had complications during the interstage period, most commonly being recurrence of infection requiring additional surgery (63 %); and 14 % of patients experienced a complication following reimplantation, most commonly persistence or recurrence of infection (59 %). While 92 % of patients that initiated treatment were ultimately reimplanted, only 69 % were infection free at 1 year and required no additional treatment. Conclusions: While two-stage exchanges for PJI in THA have been reported as successful, there are few reports of the complications during the process. In our series, significant numbers of patients experienced complications, often during the interstage period, highlighting the morbidity of this method of treatment.